The globel structure of the scale of health education and occupational risks Among the nurses working in the Algerian public health sector - Bendellalou, Houssem eddine; Bouguessa, Omar (Journal of Human Sciences, 2022)
The study aimed to study the global structure of the healthy culture scale and the occupational accident scale among workers in the public health sector , and in order to achieve its objectives , a practical model for both scale was developed , where the first included15 phrases and the second measure 10 phrases were distributed on a sample of 140 individual nurses working in the hospital Brother Boukhsham in the municipality of Oued Athmania , Mila state , depending on the statistical package for social science (spss) to analyze the data obtained through the AMOS program (Analyses of Moment Structure) , and after the data analyses process it was found that the two measures are environmentally friendly globalization and this is confirmed by the results of the proximity and high reliability while not achieving differential honesty.